Expression studies of catalytic antibodies. - Ulrich, H D (1995)
We have examined the positive influence of human constant regions on the folding and bacterial expression of active soluble mouse immunoglobulin variable domains derived from a number of catalytic antibodies. Expression yields of eight hybridoma- and myeloma-derived chimeric Fab fragments are compared in both shake flasks and high density fermentations. In addition the usefulness of this system for the generation of in vivo expression libraries is examined by constructing and expressing combinations of heavy and light chain variable regions that were not selected as a pair during an immune response. A mutagenesis study of one of the recombinant catalytic Fab fragments reveals that single amino acid substitutions can have dramatic effects on the expression yield. This system should be generally applicable to the production of Fab fragments of catalytic and other hybridoma-derived antibodies for crystallographic and structure-function studies.